Frequency shift properties of a calcium beam optical clock - Chen, Yu; Su, Yabei; Ma, Jiyang; Peng, Jing; Ma, Ming; Xue, Xiaobo; Zhang, Shengkang (Frontiers in Physics, 2025)
The optical frequency transitions with long-lifetime spin triplet states produced by the two valence electrons in the outermost layer of alkaline earth atoms make calcium atom a promising quantum frequency reference. Electron-shelving detection improves the signal-to-noise ratio of the clock transition spectrum, enabling a calcium atomic beam optical frequency standard. This scheme employs the 1S0-1P1 transition at 423 nm to detect the 1S0-3P1 transition at 657 nm, emphasizing the importance of 423 nm laser stability. While the performance of these clocks is well-studied, research on the atomic beam itself is limited. This study investigates frequency shifts in neutral calcium atoms’ 1S0-1P1 transition at 423 nm and their 1S0-3P1 transition at 657 nm. We measure the frequency shift caused by temperature, laser power, and laser alignment, providing insights to optimize the design of the calcium beam’s physical apparatus.